3v-19=6v-52

Simple and best practice solution for 3v-19=6v-52 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3v-19=6v-52 equation:


Simplifying
3v + -19 = 6v + -52

Reorder the terms:
-19 + 3v = 6v + -52

Reorder the terms:
-19 + 3v = -52 + 6v

Solving
-19 + 3v = -52 + 6v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-6v' to each side of the equation.
-19 + 3v + -6v = -52 + 6v + -6v

Combine like terms: 3v + -6v = -3v
-19 + -3v = -52 + 6v + -6v

Combine like terms: 6v + -6v = 0
-19 + -3v = -52 + 0
-19 + -3v = -52

Add '19' to each side of the equation.
-19 + 19 + -3v = -52 + 19

Combine like terms: -19 + 19 = 0
0 + -3v = -52 + 19
-3v = -52 + 19

Combine like terms: -52 + 19 = -33
-3v = -33

Divide each side by '-3'.
v = 11

Simplifying
v = 11

See similar equations:

| -u/8=42 | | 1y+9=15 | | 9=s/3-6 | | -24-3= | | 2x-9=7x-89 | | 10s-95=4s-23 | | 18=3(18)-36 | | y=3-5/2x | | 3z-36=z | | 80/2= | | 3b=10b-84 | | 2t+4+2t-3t=2+2 | | x^2-18x+26=-6 | | -2*0(0+2-5)+3(-5*0+2*2)+2(6*0+2-8)= | | 3a-69=a+13 | | 4v-51=v | | 10=4+2k | | 10v-51=v+57 | | 5(6x-1)+4(11-5x)-3(3x+3)=-6 | | 2q-79=q-28 | | 2s-4=s | | 8u-1=5u+14 | | 10c-20=c+34 | | s+3=2s | | 6+3g=18 | | 84=6(d+10) | | 5(m-73)=80 | | (5x+1.3y)+(2.9x-0.6y)= | | -19x+23x=44 | | 4*x+3=43 | | 1/3(2p-1) | | 7/42=49 |

Equations solver categories